Implementasi Kebijakan Program Badan Usaha Milik Desa (BUMDES) di Desa Hulawa Kecamatan Paguyaman Kabupaten Boalemo - sintiya hintalo; Asna Aneta; Rustam Tohopi (UIR Press, 2024)
Based on the study, implementing the Village-Owned Enterprise Program (BUMDes) Policy in Hulawa Village, Paguyaman Sub-district, Boalemo regency, has followed Hulawa Village Regulation number 3 of 2017. These are viewed from the perspective of communication, resources, implementing attitude/disposition, and bureaucratic structure. In its implementation, several problems were still found, namely the lack of ability of policy implementers to carry out existing programs, lack of communication and ccordination between policy makers and policy implementers, and the absence of a clear and structured organizational structure. It can be concluded that the implementation of the Village-Owned Enterprises (BUMDes) Program Policy in Hulawa Village, Paguyaman Sub-district, Boalemo Regency, has not been implemented optimally following existing regulations. Several things still need to be improved, such as aspects of communication, resources,implementing attitude/disposition, and bureaucratic structure.